2010
DOI: 10.1021/jo100710h
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Cyclotrimerization of Enantiopure Iodonorbornenes Catalyzed by Pd Nanoclusters for C3 or C3v Symmetric syn-Tris(norborneno)benzenes

Abstract: C(3) or C(3v) symmetric enantiopure syn-tris(norborneno)benzenes with various functional groups were synthesized through Pd-catalyzed cyclotrimerization of enantiopure iodonorbornenes. The generality of Pd-catalyzed cyclotrimerization for syn-tris(norborneno)benzenes were well-demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…2. Enantiopure (1S, 4R)-2 was converted to syn-3 exclusively under Pd-catalysed cyclotrimerization conditions 27 . Compound 3 was hydrolysed, followed by condensation, to afford the non-conjugated bowl-shaped lactam 4.…”
Section: Synthesis Of Triazasumanenesmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Enantiopure (1S, 4R)-2 was converted to syn-3 exclusively under Pd-catalysed cyclotrimerization conditions 27 . Compound 3 was hydrolysed, followed by condensation, to afford the non-conjugated bowl-shaped lactam 4.…”
Section: Synthesis Of Triazasumanenesmentioning
confidence: 99%
“…Other reagents were used as received without further purification. Both enantiomers of compound 2 and compound 3 were prepared according to our reported method 27 Ar atmosphere. The mixture was stirred at 25 °C for 8 h, during which the colour changed from yellow to dark red.…”
Section: Materials and Characterizationmentioning
confidence: 99%
“…As in the synthesis of sumanene, Pd-catalyzed syn-selective cyclotrimerization yielded syn-tris(norborneno)benzene 126 [146][147][148]. This newly developed protocol is more efficient than the conventional method reported in Scheme 36.…”
Section: Scheme 35mentioning
confidence: 93%
“…Therefore, economical and environmental oxidants have been developed. To date, numerous transition-metalcatalyzed aerobic oxidations of alcohols have been developed, such as palladium [15,16], gold [17] and ruthenium [18]. Besides, Uyanik [19] found that the catalytic system consisting of HBr/NaNO 2 was effective for the aerobic oxidation of alcohols.…”
Section: Introductionmentioning
confidence: 99%